Mismatches in the ecosystem services-wellbeing nexus: a case study for Chilean Patagonia - Felipe Benra; Laura Nahuelhual; María R. Felipe-Lucia; Rachel R. Y. Oh; Jana Kachler; Aletta Bonn (Ecosystems and People, 2023)
ABSTRACTThe supply of ecosystem services (ES) is commonly assumed to be linked to human wellbeing within socio-ecological systems. However, these linkages are seldom assessed using quantitative approaches at large scales and low spatial resolution. Here, we investigated the complex bidirectional linkages between ES supply and material wellbeing (income) using data from 382,199 rural properties in 178 municipalities from Chilean Patagonia. We assessed two model groups using structural equation modeling (SEM), wherein the first group assumed an impact of ES supply on wellbeing and the second postulated the opposite impact, with wellbeing affecting ES supply. For each group we run a separate SEM per ES category (i.e. provisioning, regulating, and cultural), making a total of six SEM analyzed. We found that neither model group was significantly stronger than the other, as the linkage between ES supply and material wellbeing was not significant in any model. Each model differed notably in their significant path coefficients, with models for cultural and regulating ES showing a better fit than for provisioning ES. We therefore assert that previously assumed links between ES and material wellbeing do not necessarily hold at larger spatial scales and in contexts where rural economies are more diverse and less dependent on natural capital. Understanding ES supply-wellbeing dynamics and how they vary across spatial and temporal scales is important for fostering sustainable socio-ecological systems.